Optimization of a product batch quantity - Berlec, Tomaž (Strojniški vestnik, 2014)
Companies encounter various challenges when entering the global market, one of the most significant being the calculation of the optimalbatch quantity of a product. This paper explains how to calculate the optimal batch quantity using first the basic model, and then the extendedmodel that takes into account the tied-up capital in a production, in addition to the costs of changing the batch and storage costs. There is acase study of calculating the optimal batch quantity using the basic and extended models, together with conclusions regarding when either ofthe two models should be used. For optimal batch quantities we also calculated lead times, corresponding costs of tied-up capital per piece,and the difference between costs per piece when using the basic and extended models.
Keywords: čas izvedbe; čas na enoto mere; čas prehoda; optimalna serija; pretočni čas; pripravljalni čas; skladiščni stroški; vezava kapitala